Adverse health effects of 5G mobile networking technology under real-life conditions - Kostoff, Ronald N.; Heroux, Paul; Aschner, Michael; Tsatsakis, Aristides (Toxicology letters, 2020)
[Display omitted] •Identifies wide-spectrum of adverse health effects of non-ionizing non-visible radiation.•Most laboratory experiments were not designed to identify the more severe adverse effects reflective of real-life conditions.•Many experiments do not include the real-life pulsing and modulation of the carrier signal.•Vast majority of experiments do not account for synergistic adverse effects of other toxic stimuli with wireless radiation.•5G mobile networking technology will affect not only the skin and eyes, but will have adverse systemic effects as well. This article identifies adverse effects of non-ionizing non-visible radiation (hereafter called wireless radiation) reported in the premier biomedical literature. It emphasizes that most of the laboratory experiments conducted to date are not designed to identify the more severe adverse effects reflective of the real-life operating environment in which wireless radiation systems operate. Many experiments do not include pulsing and modulation of the carrier signal. The vast majority do not account for synergistic adverse effects of other toxic stimuli (such as chemical and biological) acting in concert with the wireless radiation. This article also presents evidence that the nascent 5G mobile networking technology will affect not only the skin and eyes, as commonly believed, but will have adverse systemic effects as well.